Tradisi Tiatiki dan Pemimpin Opini: Analisis Media Vernakular dalam Komunikasi, Pelestarian Lingkungan, dan Politik Lokal Papua - Nurul Hidayat; Joko Utomo Hadibroto (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
The Tiatiki tradition in Teluk Depapre, Papua, is not merely an ecological ritual but serves as a cultural communication medium that conveys social and political messages. This study aims to analyze Tiatiki as vernacular media representing environmental conservation while articulating the resistance of indigenous communities against development policies that potentially threaten their customary territories. The research employs a qualitative approach with vernacular discourse analysis methods. Primary data were sourced from a 22-minute-22-second documentary produced by the Balai Pelestarian Nilai Budaya Papua (2020), analyzed through narrative transcription, identification of visual symbols, open coding, axial coding, and theoretical interpretation based on the Two-Step Flow theory and the concept of vernacular media. The findings reveal that the ritual prohibition symbolized by the “kayul larangan” is not merely a sign of marine closure for ecological purposes but also a political statement asserting indigenous territorial claims. Indigenous opinion leaders play a strategic role as cultural communicators and as drivers of subtle resistance against external interventions. These results affirm that local wisdom-based conservation in Papua is not solely ecological but also constitutes a political discourse arena projecting cultural identity and indigenous rights. This study contributes theoretically to cultural communication studies, particularly in analyzing vernacular media as instruments of local political resistance.